Assessment of Pollution by Heavy Metals in the Water and Sediment of Al-Khosur River Bed - Bishree Zaidan Khaleel Agha, Ansam Ahmed Saadoon Al-Hamdany, Taha Ahmad Taha Al-Tayyar, (Pakistan Journal of Medical & Health Sciences, 2022)
The study was conducted on Al-Khosur River basin passing through the city of Mosul from the waterfalls region to its confluence with Tigris River at the Old Bridge. Six sites were selected along the river. Water and sediment samples were collected from there. The study was carried out at the laboratories of Mosul University, through the period from September 2021 A.D. to May 2022 A.D. The concentrations of heavy metals (lead, cadmium and zinc), in water and sediment were measured quarterly. The results indicated that the heavy metals in the water had the highest concentrations in the fourth site in three elements Pb, Cd and Zn, which amounted to (0.64, 0.62 and 0.49) mg/L, respectively. This can be attributed to the bad quality of the civilian subtractions and estuaries discharged in the river which contain high concentration of heavy metals. The results also indicated high rates of heavy metals in the sediments at the fourth site as it reached the concentration of (3.18, 0.92 and 2.85) mg/kg, for Pb, Cd and Zn, respectively. The concentrations of heavy metals in the sediments increased four times for lead and zinc and two times for cadmium due to the increment in water and the contact period between water and sediment due to undecomposition for heavy metals. Keywords: Heavy metals, Al-Kosur River, Mosul environment, Water, Sediment.